2021
DOI: 10.1186/s13058-021-01488-7
|View full text |Cite
|
Sign up to set email alerts
|

Triptonide effectively inhibits triple-negative breast cancer metastasis through concurrent degradation of Twist1 and Notch1 oncoproteins

Abstract: Background Triple-negative breast cancer (TNBC) is highly metastatic and lethal. Due to a lack of druggable targets for this disease, there are no effective therapies in the clinic. Methods We used TNBC cells and xenografted mice as models to explore triptonide-mediated inhibition of TNBC metastasis and tumor growth. Colony formation assay was used to quantify the tumorigenesis of TNBC cells. Wound-healing and cell trans-well assays were utilized t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…After that, sections were incubated with HRP-labeled goat anti-rabbit secondary antibody (1:1000, Abcam) with sustaining for 30 minutes, stained with 3, 3-diaminobenzidine tetrahydrochloride (DAB) and counterstained with hematoxylin. A light microscope (Olympus Corp., Tokyo, Japan) was used to observe the images [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…After that, sections were incubated with HRP-labeled goat anti-rabbit secondary antibody (1:1000, Abcam) with sustaining for 30 minutes, stained with 3, 3-diaminobenzidine tetrahydrochloride (DAB) and counterstained with hematoxylin. A light microscope (Olympus Corp., Tokyo, Japan) was used to observe the images [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…LRP6 is a coreceptor of Wnt/β-catenin signaling, our experiments have demonstrated that CA directly targeting LRP6 inhibits EMT in breast cancer through Wnt/β-catenin signaling. Previous studies showed that TGF-β and Notch1 pathways play important roles in tumor metastasis (Sulaiman et al, 2021;Zhang et al, 2021). CA descreased expression of LRP6 but did not affect the expression of TGF-β and Notch1 (Supp.…”
Section: Discussionmentioning
confidence: 94%
“…Ionomycin is a natural product found in Streptomyces Conglobates and may be related to the activation of endonuclease in lymphocytes and the decrease of the nal apoptosis [49]. As a natural product, Triptonide can degrade oncoprotein expression and strongly inhibit Triple-negative breast cancer metastasis [50]. Among the compounds with up-regulation CSRNP1, Cyclosporine and Beclomethasone showed high-a nity docking binding energy.…”
Section: Discussionmentioning
confidence: 99%